Clinical presentation and outcome of human papillomavirus‐positive nasopharyngeal carcinoma in a North American cohort. Issue 15 (19th May 2022) - Huang, Shao Hui; Jacinto, J. C. Kennetth; O'Sullivan, Brian; Su, Jie; Kim, John; Ringash, Jolie; Spreafico, Anna; Yu, Eugene; Perez‐Ordonez, Bayardo; Weinreb, Ilan; Cho, John; Hope, Andrew J.; et al.
Abstract : Background: The objective of this study was to describe the clinical presentation and outcomes of human papillomavirus (HPV)‐positive nasopharyngeal cancer (NPC) versus Epstein–Barr virus (EBV)‐positive NPC and HPV‐positive oropharyngeal cancer (OPC). Methods: Clinical characteristics and presenting signs/symptoms were compared between patients who had viral‐related NPC versus viral‐related OPC treated with intensity‐modulated radiotherapy from 2005 to 2020 and who were matched 1:1 (by tumor and lymph node categories, smoking, age, sex, histology, and year of diagnosis). Locoregional control (LRC), distant control (DC), and overall survival (OS) were compared using the 2005–2018 cohort to maintain 2 years of minimum follow‐up. Multivariable analysis was used to evaluate the cohort effect. Results: Similar to HPV‐positive OPC ( n = 1531), HPV‐positive NPC ( n = 29) occurred mostly in White patients compared with EBV‐positive NPC ( n = 422; 86% vs. 15%; p < .001). Primary tumor volumes were larger in HPV‐positive NPC versus EBV‐positive NPC (median volume, 51 vs. 23 cm 3 ; p = .002), with marginally more Level IB nodal involvement. More patients with HPV‐positive NPC complained of local pain (38% vs. 3%; p = .002). The median follow‐up for the 2005–2018 cohort was 5.3 years. Patients who had HPV‐positive NPC ( n = 20) had rates of 3‐year LRC (95% vs. 90%; p = .360), DC (75% vs. 87%; p = .188), and OS (84% vs. 89%; p = .311) similar to the rates in those who had EBV‐positive NPC ( n = 374). Patients who had HPV‐positive NPC also had rates of LRC (95% vs. 94%; p = .709) and OS (84% vs. 87%; p = .440) similar to the rates in those who had HPV‐positive OPC ( n = 1287). The DC rate was lower in patients who had HPV‐positive disease (75% vs. 90%; p = .046), but the difference became nonsignificant ( p = .220) when the analysis was adjusted for tumor and lymph node categories, smoking, and chemotherapy. Conclusions: HPV‐positive NPC and EBV‐positive NPC seem to be mutually exclusive diseases. Patients who have HPV‐positive NPC have greater local symptom burden and larger primary tumors but have similar outcomes compared with patients who have EBV‐positive NPC or HPV‐positive OPC. Abstract : Human papillomavirus (HPV)‐positive nasopharyngeal carcinoma (NPC) and Epstein–Barr virus (EBV)‐positive NPC seemed to be mutually exclusive diseases, and p16/HPV testing was helpful in EBV‐negative NPC to elucidate potential viral etiology. HPV‐positive NPC presented with a greater local symptom burden compared with EBV‐positive NPC and HPV‐positive oropharyngeal carcinoma, but outcomes were similar.